Modeling and Meshing Analysis of 3-DOF Spherical Gear - Litong Zhang; Xianting Lu; Dashun Zhang; Baichao Wang; Zhenquan Xu (Jixie chuandong)
The 3-DOF spherical gear is proposed and its tooth surface is composed of involute ring tooth surface and semi-spherical bevel tooth surface， the error-free transmission can be realized. Based on the involute forming principle and the coordinate transformation theory， the curved surface equations of annular tooth and arc tooth are derived. According to the meshing principle and motion analysis， the conjugate tooth surface of the arc tooth surface is obtained. The simulation tooth surface and 3D model of 3-DOF spherical gear are obtained by computer， the correctness of tooth surface equation is verified. The basis for the kinematics and dynamics analysis of the 3-dof spherical gear mechanism is provided.